Acupuncture mediates the “gut–testis axis” to improve asthenozoospermia - Hao, Jianheng; Xu, Huichao; Chang, Boya; Ren, Jia; Wang, Haijun; Ji, Laixi (Frontiers in Endocrinology, 2025)
BackgroundAsthenozoospermia is a common cause of male infertility. Studies have shown that sperm quality and motility are affected by the gut–testis axis that can regulate testicular metabolism and function through the gut microbiota and its metabolites. Acupuncture is an important modality of complementary and alternative medicine. It can improve sperm motility, but it remains unclear whether acupuncture can enhance sperm vitality by influencing the gut–testis axis.MethodsIn this study, sperm quality, testicular pathology, and serum hormone levels were assessed using a cyclophosphamide-induced mouse model. Real-time PCR, a western blot analysis, and immunofluorescence techniques were used to assess the effects of acupuncture on the gut barrier and blood–testis barrier functions. In addition, gut microbiome and metabolomics were used to study the impact of acupuncture on the gut microbiota structure, serum, and testicular metabolites in asthenozoospermic mice. Further validation was obtained by performing a fecal microbiota transplantation (FMT).ResultsAcupuncture improved the sperm quality; ameliorated testicular pathology; increased serum testosterone (T), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) levels; and repaired gut and blood–testis barrier damage in asthenozoospermic mice. The abundances of Bacteroidota, Firmicutes, Faecalibaculum, and Dubosiella were associated with sperm motility, as shown by a gut microbiome analysis. Serum metabolomics revealed that differentially expressed metabolites (DEMs), such as cytosine and N-oleyl-leucine, were closely related to sperm motility. Testicular metabolomics analysis revealed DEMs, such as 5-fluorouridine and 1-acetylimidazole, were also associated with sperm motility. Furthermore, reproductive function improvements in asthenozoospermic mice through acupuncture were achieved via an FMT.ConclusionAcupuncture may alleviate asthenozoospermia symptoms by modulating the gut–testis axis and repairing the gut–testis barrier.